2019
DOI: 10.3389/fpsyg.2019.00652
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Benefits From a Musical Activity in Older Adults

Abstract: The aging population is growing rapidly. Proposing interventions that enhance the cognitive functions or strategies that delay the onset of disabilities associated with age is a topic of capital interest for the biopsychosocial health of our species. In this work, we employed musical improvisation as a focal environmental activity to explore its ability to improve memory in older adults. We present two studies: the first one evaluated neutral memory using the Rey Complex Figure (RCF) and the second one evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 80 publications
3
30
1
10
Order By: Relevance
“…Este efecto neurofisiológico es la causa por la cual se ha podido establecer una estrecha relación entre la música, la memoria y las emociones Diaz Abrahan, Shifres et al, 2019;Judde y Rickard, 2010;Justel y Rubinstein, 2013;Rickard et al, 2012). A partir de la búsqueda bibliográfica realizada se encontraron ocho estudios que cumplían con los criterios de inclusión, los cuales serán desarrollados a continuación.…”
Section: Músicaunclassified
See 3 more Smart Citations
“…Este efecto neurofisiológico es la causa por la cual se ha podido establecer una estrecha relación entre la música, la memoria y las emociones Diaz Abrahan, Shifres et al, 2019;Judde y Rickard, 2010;Justel y Rubinstein, 2013;Rickard et al, 2012). A partir de la búsqueda bibliográfica realizada se encontraron ocho estudios que cumplían con los criterios de inclusión, los cuales serán desarrollados a continuación.…”
Section: Músicaunclassified
“…Los autores encontraron que las personas que participaron de la improvisación recordaron más información tanto neutra como emocional en comparación a los otros grupos. Resultados similares fueron hallados en una investigación con adultos mayores (Diaz Abrahan, Shifres et al, 2019).…”
Section: Músicaunclassified
See 2 more Smart Citations
“…In a recent review, Schneider et al (2019) found that older musicians outperformed non-musicians in either speed or accuracy in cognitive batteries across studies. Furthermore, older adults who played a musical instrument frequently were less likely to develop dementia (Verghese et al, 2003) and have been shown to have a better visual memory (Diaz Abrahan et al, 2019). Taken together, these studies suggest that music training has a neuroenhasive and neuroprotective effect on cognition.…”
Section: Behavior and Neurophysiology In Older Adult Musiciansmentioning
confidence: 81%